Activity-specific metabolic rates for diving, transiting, and resting at sea can be estimated from time-activity budgets in free-ranging marine mammals - Jeanniard-du-Dot, Tiphaine; Trites, Andrew W.; Arnould, John P. Y.; Speakman, John R; Guinet, Christophe (Ecology and Evolution, 2017)
International audience Time and energy are the two most important currencies in animal bioenergetics. Howmuch time animals spend engaged in different activities with specific energetic costsultimately defines their likelihood of surviving and successfully reproducing. However,it is extremely difficult to determine the energetic costs of independent activities forfree-ranginganimals. In this study, we developed a new method to calculate activity-specificmetabolic rates, and applied it to female fur seals. We attached biologgers(that recorded GPS locations, depth profiles, and triaxial acceleration) to 12 northern(Callorhinus ursinus) and 13 Antarctic fur seals (Arctocephalus gazella), and used a hierarchicaldecision tree algorithm to determine time allocation between diving, transiting,resting, and performing slow movements at the surface (grooming, etc.). Weconcomitantly measured the total energy expenditure using the doubly-labelled watermethod. We used a general least-square model to establish the relationship betweentime–activity budgets and the total energy spent by each individual during their foragingtrip to predict activity-specificmetabolic rates. Results show that both species allocatedsimilar time to diving (~29%), transiting to and from their foraging grounds(~26–30%), and resting (~8–11%). However, Antarctic fur seals spent significantlymore time grooming and moving slowly at the surface than northern fur seals (36% vs.29%). Diving was the most expensive activity (~30 MJ/day if done non-stop for 24 hr),followed by transiting at the surface (~21 MJ/day). Interestingly, metabolic rates weresimilar between species while on land or while slowly moving at the surface (~13 MJ/day). Overall, the average field metabolic rate was ~20 MJ/day (for all activities combined).The method we developed to calculate activity-specificmetabolic rates can beapplied to terrestrial and marine species to determine the energetic costs of daily activities,as well as to predict the energetic consequences for animals forced to ...